Django Web Development Framework: Powering the Modern Web - Chen, Songtao; Ahmmed, Shahed; Lal, Karu; Deming, Chunhua (American Journal of Trade and Policy, 2020)
Django is a web development framework that is both powerful and flexible, and it has become an essential component in developing modern web applications. This open-source Python framework is lauded for its pragmatic design, precise code, and extensive collection of built-in features that speed up the software development process. Django's foundation is built on the "Don't Repeat Yourself" (DRY) principle, which streamlines the development of complex web applications by reducing the required duplication. Its Model-View-Controller (MVC) architectural pattern enables a clear separation of concerns, simplifying both the process of creation and the maintenance of the system. Object-relational mapping, or ORM for short, is a mechanism that Django uses to simplify and streamline database interactions by doing away with the need to perform complicated SQL queries. This review attempt will serve as a jumping-off point for our Django journey. This study will help to get started with Django by offering an overview of the fundamental principles and processes to begin building web apps.
Keywords: Django; Python; Authentication; Scalability; Modern Web Applications; DRY; Security; Reusable Components